PLANTIO DE CENOURA EM SISTEMA COM REVOLVIMENTO MÍNIMO DO SOLO - POLO, Gabriel Furlan; VENDRUSCOLO, Eduardo Pradi; LEONEL, Eduardo Augusto Souza; FIGUEIREDO, Joao Pedro Broisler; SILVA FILHO, Marcelo Xavier; SOUSA, Augusto Silva (ANAIS DO ENIC, 2022)
-